Enhancing Mechanical and Tribological Properties of Epoxy Composites with Ultrasonication Exfoliated MoS₂: Impact of Low Filler Loading on Wear Performance and Tribofilm Formation - Jayasinghe, Ravisrini; Ramos, Maximiano; Nand, Ashveen; Ramezani, Maziar (MDPI AG, 2024)
This study highlights the impact of low amounts of MoS₂ quantities on composite performance by examining the effects of ultrasonication exfoliated MoS₂ at different loadings (0.1–0.5 wt%) on the mechanical and tribological parameters of epoxy composites. Even at low concentrations, the ultrasonication and exfoliation procedures greatly improve the dispersion of MoS₂ in the epoxy matrix, enabling its efficient incorporation into the tribofilm during sliding. Optimum mechanical properties were demonstrated by the MoS₂/epoxy composite at 0.3 wt%, including a modulus of elasticity of 0.86 GPa, an ultimate tensile strength of 61.88 MPa, and a hardness of 88.0 Shore D, representing improvements of 61.5%, 35.45%, and 16.21%, respectively. Corresponding tribological tests revealed that high sliding velocity (10 N load, 0.2 m/s) resulted in a 44.07% reduction in the coefficient of friction and an 86.29% reduction in wear rate compared to neat epoxy. The enhanced tribological performance is attributed to the efficient removal and incorporation of MoS₂ into the tribofilm, where it acts as a solid lubricant that significantly reduces friction and wear. Even though an ultra-low amount of filler concentration was added to the composite, a unique finding was the high MoS₂ content in the tribofilm at higher sliding speeds, enhancing lubrication and wear protection. This study establishes that even ultralow MoS₂ content, when uniformly dispersed, can profoundly improve the mechanical and tribological properties of epoxy composites, offering a novel approach to enhancing wear resistance.
Keywords: 40 Engineering; 4016 Materials Engineering; 0912 Materials Engineering; 1007 Nanotechnology; 4016 Materials engineering; 4018 Nanotechnology